1975
DOI: 10.1161/01.cir.51.3.421
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic effects of nitroglycerin in acute myocardial infarction.

Abstract: Nitroglycerin (NTG) has recently been suggested to decrease myocardial ischemia and enhance cardiac pump function during acute myocardial infarction (AMI). To evaluate the sublingual agnet in this condition, the hemodynamic effects of 0.4 mg NTG administered to 16 supine patients during the first 72 hours of AMI were determined serially 5, 10 to 15, and 20 to 30 minutes post-NTG. Data were evaluated for the entire group, as well as for six patients with normal pulmonary artery wedge pressure (PAW) (less than o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
21
0

Year Published

1977
1977
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 177 publications
(25 citation statements)
references
References 23 publications
4
21
0
Order By: Relevance
“…Therefore, while pulmonary congestion is relieved by nitrates, cardiac output is only minimally and inconsistently influenced by these agents. '4 16,19,[23][24][25] Although hydralazine recently has been shown to improve ventricular performance by raising cardiac output, it has little to no affect on left ventricular filling pressure.27 28 While the combination of hydralazine with long-acting nitrates has been demonstrated both to improve pulmonary congestion by lowering ventricular preload and to reduce fatigue by increasing cardiac output,29' 30 oral prazosin offers the advantage of a single drug which effectively accomplishes the same therapeutic purposes without the disadvantages of hydralazine side effects.3'3 Further, our clinical experience with prazosin in heart failure therapy has indicated the agent does not cause serious untoward actions; only transient headache and mild nausea were noted in two patients which did not require discontinuance of the drug. Of additional importance is that we have not observed orthostatic hypotension with the careful and individualized use of prazosin in relieving severe heart failure symptomatology, apparently because the agent did not lower left ventricular preload below the upper limits of normal ( fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, while pulmonary congestion is relieved by nitrates, cardiac output is only minimally and inconsistently influenced by these agents. '4 16,19,[23][24][25] Although hydralazine recently has been shown to improve ventricular performance by raising cardiac output, it has little to no affect on left ventricular filling pressure.27 28 While the combination of hydralazine with long-acting nitrates has been demonstrated both to improve pulmonary congestion by lowering ventricular preload and to reduce fatigue by increasing cardiac output,29' 30 oral prazosin offers the advantage of a single drug which effectively accomplishes the same therapeutic purposes without the disadvantages of hydralazine side effects.3'3 Further, our clinical experience with prazosin in heart failure therapy has indicated the agent does not cause serious untoward actions; only transient headache and mild nausea were noted in two patients which did not require discontinuance of the drug. Of additional importance is that we have not observed orthostatic hypotension with the careful and individualized use of prazosin in relieving severe heart failure symptomatology, apparently because the agent did not lower left ventricular preload below the upper limits of normal ( fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, attempts to continue the benefits of such balanced ventricular unloading therapy in ambulatory patients with chronic heart failure have been difficult because of the lack of an oral vasodilator drug with both arteriolar and venous relaxing properties. Thus the nitrates, which principally cause venodilation, are capable of reducing ventricular preload and pulmonary congestion3' 13,14,16,19,[23][24][25][26] but lack consistent effects on systemic impedance and therefore produce minimal alterations of cardiac output …”
mentioning
confidence: 99%
“…Although the major hemodynamic effects of nitroglycerin given sublingually have been established with relative consistency by previous investigations (2,3,6,11,12,15,16,19,26,35,40,41) the efficacy of this agent when administered orally has been a subject of continuing controversy. This study demonstrates significant, prolonged hemodynamic action by controlled-release nitroglycerin.…”
Section: Discussionmentioning
confidence: 87%
“…Previous evaluation of sublingual nitroglycerin in acute myocardial infarction by our group (40) and others (11,15) has documented certain beneficial hemodynamic effects which are, however, brief in duration. Recent studies have indicated favorable hemodynamic actions for several hours by certain orally administered nitrates (1,3,40). Because of the desirability of an effective long-acting vasodilator that can be readily administered to ambulatory patients, the following study was performed in patients with acute or chronic congestive heart failure of differing etiologies to evaluate the hemodynamic effects of nitroglycerin administered orally (ONTG) in a form to produce sustained action.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation